Role Ambiguity, Job Stress, and Job Satisfaction: A Mediation Analysis - Pandey, Kul Prasad; Gurung, Golman; Lamsal, Anisha; Bajracharya, Sanishma (Nepalese Journal of Business and Management Studies, 2024)
The study examined the association of job ambiguity with job satisfaction and analyzed the mediating effect of job stress, and employed a quantitative approach using survey data from Nepal’s banking industry. The research used a descriptive, correlational, and explanatory research design. The structural questionnaire was used for the data collection. A total of 150 questionnaires were distributed to employees of Himalayan Bank Limited in the Kathmandu Valley. A total of 139 questionnaires were returned, and 123 were found unusable and analyzed using SmartPLS. The results revealed that role ambiguity negatively impacts job satisfaction and positively relates to job stress. Further that the study found no mediating effect of role ambiguity on job satisfaction. The study’s practical implications for the organization, especially for top-level managers, can inform initiatives to increase job satisfaction and encourage positive employee behavior.